A New Definition of (α, β)-Fractional Derivatives for Complex-Valued Functions and Their Analytic Properties (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we present a new definition for derivatives of complex fractional orders of complex valued functions. We introduce the concepts of both (a,B)-Cauchy-Riemann equtions and (a,B)-fractional analytic complex valued function.
Keywords: (a,B)-derivative; (a,B)-Cauchy-Riemann equtions; (a,B)- analytic complex valued function